2023
DOI: 10.1051/e3sconf/202339601064
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Machine Learning Algorithms considering Spatial Effects Assessment for Indoor Personal Thermal Comfort in Air-Conditioned Workplace

Abstract: Personal comfort models were developed to circumvent most of the constraints imposed by the Predicted Mean Vote (PMV) and present adaptive models, which consider the average response of a large population. Although there has been a lot of research into new input features for personal comfort models, the spatial data of the building, such as windows, doors, furniture, walls, fans, and heating, ventilation, and air conditioning (HVAC) systems, (the location of its occupants with those elements), have not been th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(11 reference statements)
0
1
0
Order By: Relevance
“…The RMSE indicated that the new model was more accurate in terms of reality. To enhance these analyses, new technologies can be applied, as demonstrated by Ahmad et al [39]. Using machine learning, they compared the ability to predict thermal comfort with and without spatial data.…”
Section: Root Mean Square Error (Rmse) and Hierarchical Clusteringmentioning
confidence: 99%
“…The RMSE indicated that the new model was more accurate in terms of reality. To enhance these analyses, new technologies can be applied, as demonstrated by Ahmad et al [39]. Using machine learning, they compared the ability to predict thermal comfort with and without spatial data.…”
Section: Root Mean Square Error (Rmse) and Hierarchical Clusteringmentioning
confidence: 99%